THE POSITION OF BRIDGE BANKS AS INSTRUMENTS FOR RESOLVING BANK FAILURES IN INDONESIA - Zulfikar Hasan; Kamiluddin (Bank Indonesia, 2023)
We analysed the capacity for banks to fail in Indonesia. A â€œfailed bankâ€ can be decoded as a bank facing financial difficulties and possibility of collapse. It is no longer feasible for the LPP (Banking Supervisory Agency) to address bank failures under its current authority. In Indonesia, bank failures are managed by the Deposit Insurance Corporation (IDIC), helped by rules from Bank Indonesia and the Financial Services Authority (OJK). Under Article 5 of Law no. 24 of 2004 regarding the Deposit Insurance Corporation, one of the jobs of IDIC is to develop, specify and enforce a procedure for the liquidation of failing banks that do not have a systemic effect and address failing banks that do have a systemic effect. The definition of systemic effect is when a bankâ€™s failure will have an extraordinary impact on the availability of funds and the smoothness and sustainability of the economy. While a non-systemic effect is bankâ€™s failure that does not meet the standards noted above. The implication of our research is to provide an understanding that assistance for failing banks in Indonesia is taken over by the IDIC which will form an entity called a bridge bank.